2020
DOI: 10.26803/ijlter.19.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Students Code-Switching: The Inevitable Evil in EFL Classrooms

Abstract: Code-switching has been primarily investigated in a variety of sociocultural contexts, especially in foreign and second language settings. The majority of code-switching instances, whether in teacherinitiated activities or teacher-student interaction, seem to suggest that these interactions reflect a sophisticated language use and serve a variety of pedagogical purposes. This study aims to find out the main functions and roles of code-switching among EFL high school teachers and students in Jordan. For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Therefore, one of the research gaps that this study filled was addressing CS functions by both teachers and students. Hussein et al (2020) aimed to identify CS's primary functions and roles among Jordan's EFL high school teachers and students. They applied a mixed method that included observing two EFL teachers in 12 classes and distributing an Arabic Likert-type questionnaire to 330 high school students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, one of the research gaps that this study filled was addressing CS functions by both teachers and students. Hussein et al (2020) aimed to identify CS's primary functions and roles among Jordan's EFL high school teachers and students. They applied a mixed method that included observing two EFL teachers in 12 classes and distributing an Arabic Likert-type questionnaire to 330 high school students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, they offered suggestions for how to include some aspects of native languages in educational classroom instruction. Some literature indicated that the switching of codes improves learning and instruction in academic subjects (Hussein, Saed & Haider 2020;Kusumo Adi & Ambarini 2022;Murtiningsih et al 2022;Razak & Shah 2020). Teachers frequently establish an accepting atmosphere for communicating with learners of the English language in the senior phase even if they frequently employ code-switching to teach substantive subjects in the educational setting.…”
Section: Empirical Literaturementioning
confidence: 99%
“…According to Razak & Shah (2020) codeswitching in ESL classrooms has positive impact used as a strategy to acquire the target language which is also one of the salient points of the current study. In fact, students code-switch for non-linguistic purposes such as establishing rapport and interpersonal relationships as well as maintaining the line of communication without disruption to circumvent any sort of conflict or misinterpretation (Hussein, et al, 2020). To supplement, Nurhamidah et al(2018) likewise emphasized that code-switching prevalence in ESL classroom has indeed been essential for both teachers and students.…”
Section: How Prevalent Is Codeswitching On Subjects With English As A...mentioning
confidence: 99%